2016
DOI: 10.1080/0972060x.2014.977570
|View full text |Cite
|
Sign up to set email alerts
|

Fumigant Toxicity and Nymph Production Deterrence Effect of Three Essential Oils Against Two Aphid Species in the Laboratory Condition

Abstract: Nowadays, usage of pesticides is one of the primary methods in aphids control and have an important role in pest control, but improper use of them are causing adverse effects on nontarget organisms and the environment. Essential oils due to volatility and very short-term persistence in the environment, as biocompatible pesticides can be considered as one of the alternatives to chemical pesticides in aphid's control. This study was conducted to determine the insecticidal activity and nymph production deterrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Moreover, a Mentha piperita extract resulted in maximum insecticidal activity against B. brassicae with increased concentration and time exposure 39 . Similarly, essential oil from Cinnamomum zeylannicum was found to be effective against B. brassicae, exhibiting 8.3 and 7.4 µl mL −1 LC 50 values 40 . The essential oil of another medicinal plant, Elettaria cardamomum, was reported to be effective against this serious pest, exhibiting 79.2 µl mL −1 LC 50 value 41 .…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, a Mentha piperita extract resulted in maximum insecticidal activity against B. brassicae with increased concentration and time exposure 39 . Similarly, essential oil from Cinnamomum zeylannicum was found to be effective against B. brassicae, exhibiting 8.3 and 7.4 µl mL −1 LC 50 values 40 . The essential oil of another medicinal plant, Elettaria cardamomum, was reported to be effective against this serious pest, exhibiting 79.2 µl mL −1 LC 50 value 41 .…”
Section: Discussionmentioning
confidence: 93%
“…Evaluation of the effects of seven plant EOs, including S. rosmarinus on the cabbage aphid B. brassicae , showed that they reduced reproductivity and led to an increased mortality rate in the aphid population [ 55 ]. The deterrence of aphid nymph production varied from 6.18 to 84.83% for three different EOs with LC 10 and LC 25 against Brevicoryne brassicae L. and the black aphid Aphis fabae [ 22 ]. In general, EOs as biocompatible pesticides, due to their volatility and very short-term persistence in the environment, can be considered an important alternative to chemical pesticides to control aphids [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, 100 g of the powder from each plant was used as a replicate (3 replicates) to extract the essential oils. Each 33.3 g was inserted into a 1-L flask filled with 0.5 L of distilled water and subjected to hydrodistillation using a Clevenger-type apparatus for six hours [ 22 ]. The oils were dried over anhydrous sodium sulfate to remove traces of moisture and stored at 4 °C until use.…”
Section: Methodsmentioning
confidence: 99%